“Blessed are the pure in heart, for they shall see God” (Mt 5:8) as Interpreted by the Church Fathers (4th-5th cent.) - Wygralak, Paweł (Verbum Vitae, 2020)
The article presents the statements of selected Church Fathers (4th-5th centuries) concerning the Beatitude “Blessed are the pure in heart, for they will see God” (Mt 5:8), spoken by Jesus in the Sermon on the Mount. They emphasise that during the earthly life man can only see the reflection of God if his heart is pure. Since man was created in the image and likeness of God, he carries this image in his heart, but this image was polluted by sin. Therefore, one should purify the heart by renouncing sins and developing virtues. The most important comments on this issue were expressed by St Gregory of Nyssa and St Augustine.